Bioefficacy of mosquito mat vaporizers and associated metabolic detoxication mechanisms in Aedes aegypti (Linnaeus) in Selangor, Malaysia: A statewide assessment - Taib, Azratul Hizayu (Malaysian Society of Parasitology and Tropical Medicine, 2021)
This study aims to examine the efficacy of mosquito mat vaporizers on Aedes aegypti and their associated metabolic detoxication mechanisms. For this purpose, Aedes aegypti (Linnaeus) was collected from nine districts in Selangor, Malaysia and tested with mosquito vaporizing mat bioassays. The same populations were also subjected to biochemical assays to investigate activities of detoxifying enzymes, namely non-specific esterase (EST), glutathione-S-transferase (GST) and mixed function oxidase (MFO). The efficacy of Ae. aegypti on the active ingredients tested in decreasing order were d- allethrin > dimefluthrin > prallethrin with PBO > prallethrin. The results further indicated significant enhancement mean levels of EST, GST and MFO in pyrethroid-resistant populations. The mortality rate of Ae. aegypti in response to pyrethroid active ingredients was associated with MFO activity, suggesting it is an important detoxification enzyme for the populations tested. In view of the presence of resistance against household insecticide products, pyrethroid efficacy on Ae. aegypti populations needs to be monitored closely to ensure the implementation of an effective vector control program in Malaysia.